Distinct neuroanatomical and neuropsychological features of Down syndrome compared to related neurodevelopmental disorders: a systematic review - Hamadelseed, Osama; Chan, Mike K. S.; Wong, Michelle B. F.; Skutella, Thomas (Frontiers in Neuroscience, 2023)
Objectives We critically review research findings on the unique changes in brain structure and cognitive function characteristic of Down syndrome (DS) and summarize the similarities and differences with other neurodevelopmental disorders such as Williams syndrome, 22q11.2 deletion syndrome, and fragile X syndrome. Methods We conducted a meta-analysis and systematic literature review of 84 studies identified by searching PubMed, Google Scholar, and Web of Science from 1977 to October 2022. This review focuses on the following issues: (1) specific neuroanatomic and histopathological features of DS as revealed by autopsy and modern neuroimaging modalities, (2) language and memory deficits in DS, (3) the relationships between these neuroanatomical and neuropsychological features, and (4) neuroanatomic and neuropsychological differences between DS and related neurodevelopmental syndromes. Results Numerous post-mortem and morphometric neuroimaging investigations of individuals with DS have reported complex changes in regional brain volumes, most notably in the hippocampal formation, temporal lobe, frontal lobe, parietal lobe, and cerebellum. Moreover, neuropsychological assessments have revealed deficits in language development, emotional regulation, and memory that reflect these structural changes and are more severe than expected from general cognitive dysfunction. Individuals with DS also show relative preservation of multiple cognitive, linguistic, and social domains compared to normally developed controls and individuals with other neurodevelopmental disorders. However, all these neurodevelopment disorders exhibit substantial heterogeneity among individuals. Conclusion People with Down syndrome demonstrate unique neurodevelopmental abnormalities but cannot be regarded as a homogenous group. A comprehensive evaluation of individual intellectual skills is essential for all individuals with neurodevelopment disorders to develop personalized care programs.